2018 26th European Signal Processing Conference (EUSIPCO) 2018
DOI: 10.23919/eusipco.2018.8553244
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Latent Mixture Model for Polyphonic Music Analysis

Abstract: Polyphonic music transcription is a challenging problem, requiring the identification of a collection of latent pitches which can explain an observed music signal. Many state-of-the-art methods are based on the Non-negative Matrix Factorization (NMF) framework, which itself can be cast as a latent variable model. However, the basic NMF algorithm fails to consider many important aspects of music signals such as lowrank or hierarchical structure and temporal continuity. In this work we propose a probabilistic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Waghmare et al [8] conducted a study on the classification and labeling of Indian music, proposed that Mel-frequency cepstral coefficients (MFCCs) can provide timbre information, and demonstrated the effectiveness of this method through experimental analysis. O'Brien et al [9] conducted a study on the transcription of polyphonic music and proposed a probabilistic latent component analysis model. Their experiments demonstrated that this method effectively decomposed the signal into distinct hierarchical smooth structures, resulting in high-quality transcriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Waghmare et al [8] conducted a study on the classification and labeling of Indian music, proposed that Mel-frequency cepstral coefficients (MFCCs) can provide timbre information, and demonstrated the effectiveness of this method through experimental analysis. O'Brien et al [9] conducted a study on the transcription of polyphonic music and proposed a probabilistic latent component analysis model. Their experiments demonstrated that this method effectively decomposed the signal into distinct hierarchical smooth structures, resulting in high-quality transcriptions.…”
Section: Introductionmentioning
confidence: 99%